Parathyroid hormone assay standardization in CKD-MBD: resolving heterogeneity for precision medicine - Bai, Xuanchang; Xu, Kaiduo; Ma, Zijia; Zhao, Haijian; Zhou, Weiyan; Zhang, Chuanbao (Frontiers in Endocrinology, 2025)
Parathyroid hormone (PTH) plays a crucial role in calcium homeostasis and bone metabolism. Accurate measurement of PTH is essential for diagnosing and managing various endocrine and osteological diseases, particularly in the context of chronic kidney disease-mineral and bone disorder (CKD-MBD). Current immunoassays—categorized into three generations—struggle with PTH’s molecular heterogeneity. Mass spectrometry (MS) offers structural specificity, with recent advances achieving satisfactory sensitivity for intact 1–84 PTH quantification and identifying clinically relevant fragments. This review synthesizes the technological limitations of PTH measurement methods, highlights the critical standardization challenges, and discusses evolving strategies, including MS, to pave the way for reliable PTH testing in CKD management.